2013
DOI: 10.1186/1471-2369-14-280
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic function is a strong predictor of mortality in patients with chronic kidney disease

Abstract: BackgroundCardiovascular disease is a major cause of death in patients with stage 4–5 Chronic Kidney disease (CKD, eGFR < 30). There are only limited data on the risk factors predicting these complications in CKD patients. Our aim was to determine the role of clinical and echocardiographic parameters in predicting mortality and cardiovascular complications in CKD patients.MethodsWe conducted a prospective observational cohort study of 153 CKD patients between 2007 and 2009. All patients underwent echocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 37 publications
4
53
0
3
Order By: Relevance
“…This was comparable to observations in the study conducted by Meyeon P et al 30 , who documented an increase in Left Ventricular Mass with increase in severity of the disease in CKD patients. The present study results are also comparable to study by Farshid A et al 18 …”
Section: Left Ventricular Echo Parameterssupporting
confidence: 82%
“…This was comparable to observations in the study conducted by Meyeon P et al 30 , who documented an increase in Left Ventricular Mass with increase in severity of the disease in CKD patients. The present study results are also comparable to study by Farshid A et al 18 …”
Section: Left Ventricular Echo Parameterssupporting
confidence: 82%
“…Farshid et al showed that some degree of diastolic dysfunction was present in 86% of patients on HD with a mean age of 58.7±15.0 years, and 35% had grade ≥2 diastolic dysfunction, which was a powerful independent predictor of mortality. 18 In the present study, almost all patients (i.e., those with mean age, 67.9±10.6 years) had some degree of abnormal LV filling or AF.…”
Section: Factors Of E/e'mentioning
confidence: 85%
“…Hemodialysis patients have common comorbidities (e.g., age, hypertension, diabetes mellitus, LVH, coronary artery disease, and infiltrative cardiomyopathy) often associated with the development of myocardial fibrosis and decreased ventricular compliance, which are physiopathological landmarks of diastolic heart failure (DHF) [7]. Left ventricular diastolic dysfunction (LVDD), an early stage of DHF, is a strong predictor of cardiovascular mortality and morbidity in the general population and also in patients with chronic kidney disease [8][9][10][11]. Hence, LVDD in hemodialysis patients should be promptly identified and treated so as to improvemorbidity and mortality [7].…”
mentioning
confidence: 99%